LATIHAN DRIBBLING CIRCUIT DAPAT MENINGKATKAN KETERAMPILAN DRIBBLING PEMAIN SEPAK BOLA - Eka, Lalu Sukmawan; Marzuki, Ismail (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
The dribbling ability of the Notorius Mataram club players from observations during the match and the preliminary data obtained by many players whose dribbling is still easily taken by opponents and ball control is still not good. Dribbling is a basic technique that must be mastered with good dribbling is a basic component that is needed in the game of football. In this study the authors examined the practice of dribbling circuits to improve dribbling skills. The purpose of this study was to determine the effect of dribbling circuit training on improving the dribbling skills of soccer players. The method used in this study is an experimental method with one group pretest-posttest design. In this study the authors took a sample with a population study that is using all Notorius Mataram players, amounting to 20 people. The research instrument used was a dribbling test from (Nurhasan: 2000). Based on the processing and analysis of increased data from the initial test results obtained an average value of 20.86 and the final test obtained a value of 19.31, the difference between the initial test and final test of 30.91. While the hypothesis test with a similar sample t test was obtained tcount 7.122> t table 1.729 thus Ho was rejected and Ha was accepted. Then the researchers draw conclusions, namely: There is the influence of dribbling circuit training on improving the dribbling skills of the Mataram Notorius club in 2020